The Impact of DELIKAN Learning towards Mathematics Achievement in Terms of Students Motivation: An Experiment at the State Elementary Schools of Banyumas, Central Java, Indonesia - Irianto, Sony; Eka, Karma Iswasta (EDUCARE, 2011)
ABSTRACT: This research is aimed at finding out the difference between the Mathematics achievement of the students taught using DELIKAN (Dengar, Lihat, Kerjakan or Listening, Looking, Doing) learning and those taught using Conventional one; the difference in Mathematics due to the difference in the level of motivation; and the interrelationship of Mathematics achievement as caused by DELIKAN learning, conventional learning, and motivation. This research was carried out in State Elementary School of Pasir Wetan and State Elementary School 2 of Kecila in the even semester of the academic year of 2009/2010. The method used was experiment with factorial design of 2 x 2. The population was the fourth year students of both Elementary Schools. Data was collected through multiple choice objective test and questionnaire to measure motivation. The result of the analysis showed that the there was a significant difference in the mathematics achievement of students taught using DELIKAN and those taught with conventional learning; there was not significant difference in mathematics achievement as a result of difference in motivation; and there was not significant interrelationship in mathematics achievement as caused by DELIKAN, conventional learning, and motivation.KEY WORDS: DELIKAN learning, conventional, motivation, Elementary Schools, and Mathematics achievement.Â Â About the Authors: Sony Irianto and Karma Iswasta Eka are the Lecturers at the Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto), Jalan Raya Dukuhwaluh PO Box 202, Purwokerto 53182, Central Java, Indonesia. They can be reached at: tukiranump@yahoo.comHow to cite this article? Irianto, Sony & Karma Iswasta Eka. (2011). âThe Impact of DELIKAN Learning towards Mathematics Achievement in Terms of Students Motivation: An Experiment at the State Elementary Schools of Banyumas, Central Java, Indonesiaâ in EDUCARE: International Journal for Educational Studies, Vol.3(2) February, pp.187-194. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 17, 2010); Revised (January 18, 2011); and Published (February 17, 2011).